If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2x + 7 = 0 Reorder the terms: 7 + 3x + -2x = 0 Combine like terms: 3x + -2x = 1x 7 + 1x = 0 Solving 7 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 0 + -7 1x = 0 + -7 Combine like terms: 0 + -7 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 20*x=0.5 | | 3/4(24-8b)=2(5b-1) | | NO=5x+12 | | -4+f=6f+26 | | 6y^2-21y-291=0 | | 3x-3+3x-3=x+7+x+7 | | 12x-15-4x-4=12x-8+5 | | 7x-5=4x-11 | | 7m-13m=138 | | (4x-1/2)2 | | -x+8*0=40 | | 15x-15-4x+8=-2x-4 | | -0+8y=40 | | 15x-15-4x+8=-2x-2 | | 9x-4*0=54 | | 9*0-4y=54 | | 6x(2/3) | | -13x-0=39 | | -13*0-y=39 | | 2p+5=-9 | | 3x-12+5=2x+13 | | 10z+2=5 | | 5p+pq+6pr= | | Y=2X-40 | | -x-5*0=12 | | 36x+5(9x-x)-3x= | | 2X-40=1Y | | -0-5x=12 | | (2X-40)=Y | | 5x-91=-11 | | Logx=18.8 | | 7x-12x-5=-42+15 |